HUBUNGAN PENGUASAAN BUNKEI DENGAN KEMAMPUAN SAKUBUN SISWA KELAS XI SMA NEGERI 12 PADANG TAHUN AJARAN 2017/2018 - Dini Dwianti Nur Fadhilla; Desvalini Anwar; Meira Anggia Putri (Universitas Negeri Padang, 2018)
This research aims to determine whether there is or not a significant relationship between students’ bunkei mastery and students’ sakubun’s ability at class XI IPA Negeri 12 Padang. The method of this research is quantitative research with descriptive correlational type. The data collected in this study was obtained from 2 tests: the multiple choice question to test the students’ bunkei mastery and essay test to test the studets’ sakubun mastery. Based on the research data, obtained the result of student’s bunkei mastery are at a score of 81.62 and student’s sakubun ability are at a score of 71.63, meaning strong category. From the data of both variables above, obtained correlation value of 0.725. This proves that H0 is rejected and H1 accepted, it means there is a significant relationship between student’s bunkei mastery with sakubun ability.Keywords: correlation, bunkei, sakubun